Optimizing Sustainability: Design, Fabrication, and Experimental Assessment of a Biogas Plant for Renewable Energy Generation (International Journal of Communication Systems and Network Technologies, 2020)
This paper presents a comprehensive study on the design, fabrication, and experimental assessment of a biogas plant aimed at optimizing sustainability and renewable energy generation. The increasing demand for clean and sustainable energy sources has prompted a focus on harnessing biogas from organic waste materials. The proposed biogas plant integrates innovative design principles, meticulous fabrication processes, and a rigorous experimental assessment to evaluate its performance. The design phase involves the development of an efficient anaerobic digestion system, ensuring optimal biogas production from diverse organic feedstocks. The fabrication process emphasizes the use of cost-effective and environmentally friendly materials, aligning with the plant’s overarching sustainability goals. To assess the plant’s performance, a series of experiments are conducted, measuring critical parameters such as biogas production rates, methane content, and process stability. The experimental results are analyzed to evaluate the plant’s efficiency, reliability, and its potential as a viable renewable energy solution. This research contributes to the growing body of knowledge in sustainable energy systems by providing insights into the design intricacies, fabrication methodologies, and the real-world performance of a biogas plant. The findings offer valuable information for researchers, engineers, and policymakers seeking to advance renewable energy technologies and promote environmentally conscious solutions for energy generation.
Keywords: Counter-based Trimming; Precision Machining; Depth Control; 3-Axis Gyroscope; Automated Trimmer System; Adaptive Machining; Surface Contour Mapping; Gyroscope Integration; Dynamic Cutting Depth; Precision Manufacturing